On Pacific economic integration. - YAMAZAWA, Ippei (1992)
Discusses the characteristics of economic integration in the Pacific, which is different in form and extent from that in Europe and North America. Notes that the word 'integration' is perhaps too strong in popular usage to describe its regionalism and may be better replaced by 'cooperation'.